Validation, revision and extension of the Mantle Cell Lymphoma International Prognostic Index in a population-based setting - Saskia A.M. van de Schans; Maryska L.G. Janssen-Heijnen; Marten R. Nijziel; Ewout W. Steyerberg; Dick Johan van Spronsen (Haematologica, 2010)
Background The aim of this study was to validate the Mantle Cell Lymphoma International Prognostic Index in a population-based cohort and to study the relevance of its revisions.Design and Methods We analyzed data from 178 unselected patients with stage III or IV mantle cell lymphoma, registered between 1994 and 2006 in the Eindhoven Cancer Registry. Follow-up was completed up to January 1st, 2008. Multiple imputations for missing covariates were used. Validity was assessed by comparing observed survival in our cohort with predicted survival according to the original Mantle cell lymphoma International Prognostic Index. A revised model was constructed with Cox regression analysis. Discrimination was assessed by a concordance statistic (‘c’).Results The original Mantle cell lymphoma International Prognostic Index could stratify our cohort into three distinct risk groups based on Eastern Cooperative Group performance status, white blood cell count, lactate dehydrogenase level, and age, with the discrimination being nearly as good as in the original cohort (c 0.65 versus 0.63). A modified model including performance status in five categories (0/1/2/3/4) instead of two (0–1/2–4), the presence of B-symptoms (yes/no) and sex (male/female) in addition to the original variables resulted in a better prognostic index (c 0.75).Conclusions The Mantle cell lymphoma International Prognostic Index is a valid tool for risk stratification, comparison of prognosis, and treatment decisions in an unselected Dutch population-based setting. Although the index can be significantly improved, external validation on an independent data set is warranted before broad application of the modified instrument could be recommended.